'Chaos, Through a Veil of Order': The Dialectic of Theory and Spontaneity in Psychoananalytic Work. (14th October 2014) - Holmes, Jeremy
<x xml:space="preserve">Abstract</x> The theme of the paper is the quotidian debate about the role of theory in analytic practice. Based on examples from recent psychoanalytic publications, I argue that psychoanalytic theory may influence therapists as ideology, heuristics, or empiricism, or combinations thereof. Bion's eschewing of theory, and advocacy of an analytic stance 'beyond memory and desire' as a precondition for psychoanalytic creativity is questioned. Buber's advocacy of I–Thou relatedness is compared with the concept of mentalizing, and related to recent findings in developmental psychopathology. Parallels are drawn between the therapeutic relationship – bringing together theory and spontaneity in a hermeneutic enterprise – and the infant's use of security‐promoting care‐givers.